A novel hydraulic transmission solution to large offshore wind turbine: Design and control strategy. (1st July 2022) - Wang, Feng; Chen, Jincheng; Cheng, Min; Xu, Bing
Abstract: As a comparative solution to gearbox transmission, the hydrostatic transmission has potential to improve offshore wind turbine reliability. However, drivetrain efficiency of hydrostatic transmission is relatively low at low wind speed. To solve this problem, a digital hydrostatic transmission solution for large offshore wind turbine is proposed. The large variable displacement motor in hydrostatic transmission is replaced by multiple fixed displacement motors and a small variable displacement motor. However the wind is turbulent in nature. This results in frequent switching of fixed displacement hydraulic motors. Therefore in this study a control strategy of large utility digital hydrostatic wind turbine under turbulent wind is proposed. The torque control of digital hydrostatic wind turbine is presented. The digital displacement switching scheme is developed. The system pressure controls during motor switching are studied. The dynamic performances and annual energy production of digital hydrostatic wind turbine under turbulent wind are studied. Results show the effectiveness of the proposed control strategy for digital hydrostatic wind turbine. The mean turbine output power at different mean wind speeds of hydrostatic and digital hydrostatic wind turbines are studied and compared. Results show the digital hydrostatic wind turbine has a 1.6% annual energy production improvement than the hydrostatic wind turbine. Highlights: A control strategy for digital hydrostatic wind turbine under turbulent wind is developed. The digital displacement switching scheme of digital hydrostatic wind turbine is proposed. The system operations during fixed displacement motor switching are presented. The effectiveness of proposed control strategy is verified through simulation study. The turbine output power under turbulent wind is higher than conventional hydrostatic wind turbine.